Reconversão cultural nas narrativas dos egressos do programa de ações afirmativas da Universidade Federal do Rio Grande do Sul - Santos, Rosemeri Antunes dos (2017)
The central theme of this research are the narratives of graduate students from the Federal University of Rio Grande do Sul who participated in the Affirmative Action Programme. Guided by a Bourdieusian perspective, we also focus on social trajectories, knowledge construction and the reconversion of cultural capital and habitus. Through their memories, we set out to examine the experiences of these students within the institutionalized Programme that was established in 2007 and sanctioned a quota system through which candidates were granted admission to this university into reserved places. The Affirmative Action Programme was reassessed in 2012 and the Quota Policy was renewed for 10 more years. In the same year, Federal Law n° 12.71/2012 was sanctioned, guaranteeing that 50% of all places at the undergraduate level in federal universities be reserved for ‘quota candidates’ until 2016. The time period chosen for our research on 'quota student' admission spans 4 years, between 2008 and 2012. Our theoretical framework was anchored by the concept of social memory, as well as the Bourdieusian concepts of habitus, class and cultural capital. In three data bases, a literary review was carried out concerning the topic of our research, in publications issued between 2010 and 2015. Results showed the novelty of our particular focus on graduate students and memory narrative. Regarding our methodology, which is applied to oral history, we developed research that is both quantitative and qualitative, of the bibliographic, documentary and exploratory type. Online questionnaires were sent to all graduates with diplomas, and samples from 155 of these participants were collected, along with 10 theme-centred interviews. The obtained data was analyzed and interpreted in accordance with graphs and the technique of content analysis. The results of our research show that the experiences of this sample of ‘quota students’ provided for a resignification of their cultural capital and habitus. Our research data show that the graduates perceive the Affirmative Action Programme at UFRGS as a positive inclusive education policy as well as an advance in ethnic and racial relations in the university environment. Additionally, we observed that these graduates seem to consider their participation in the Programme as a significantly important opportunity which has influenced their social trajectory. The final product of our study was systemized in a video entitled "The Voices of Quota Graduates from UFRGS".